Obcy w poszukiwaniu domu: Księgi Jakubowe Olgi Tokarczuk dla współczesnej Ukrainy, Polski, Europy - Sływynski, Ostap (Postscriptum Polonistyczne, 2020)
The essay discusses Olga Tokarczuk’s novel Books of Jacob in the context of the topos of journey, featuring in the author’s earlier texts in various ways. Journey becoming an escape represents earlier approaches to this topos, which already focused on the figure of the Other. This becomes accentuated in the Books of Jacob which conveys a vital thought for the contemporary world by constructing an all inclusive narrative, encompassing different religions, nationalities and ethnic groupings. This is an important message, especially for the societies of Poland and Ukraine, nations who are in search for a new identity, which could secure a safe ideological and geopolitical “home”.